Вплив органічних кислот на синтез мікробного полісахариду етаполану на суміші С2-С6-субстратів - Пирог, Тетяна Павлівна; Гарбарчук, С. О.; Савчук, Оксана Миколаївна (My University, 2012)
Нейтралізація культуральної рідини органічними кислотами під час культивування Acinetobacter sp. ІМВ B-7005 на суміші ацетату і меляси супроводжувалася підвищенням на 17–40 % показників синтезу етаполану і у 7–9 разів в’язкості його розчинів за присутності катіонів К+ і системі Cu2+-гліцин порівняно з показниками процесу без регуляції рН. Етаполан з такими властивостями може використовуватися для інтенсифікації нафтовидобутку. The Acinetobacter sp. IMV В-7005 cultivation conditions on mixture of acetate and molasses providing the maximal transformation of the substrate carbon in the microbial exopolysaccharide ethapolan were established. The use of the soluble organic acids (acetic, citric, succinic, oxalic) for neutralization of cultural liquid under Acinetobacter sp. IMV В-7005 cultivation on mixture of acetate and molasses was accompanied by increasing (17–40 %) of ethapolan synthesis indices and enhancing (7–9 fold) the viscosity its solutions in the presence of 0,1 M К+ and Cu2+-glycine system as compared to process realization without pH regulation. Maximal of ethapolan synthesized quantity (12,4–12,9 g/l) were obtained when acetic acid was used for neutralization of Acinetobacter sp. IMV В-7005 cultural liquid. Ethapolan with improved rheological properties can be used for the oil recovery intensification.
Keywords: екзополісахариди; інтенсифікація біосинтезу; органічні кислоти; регуляція рН; в’язкість; exopolysaccharides; biosynthesis intensification; organic acids; regulation of pH; viscosity; кафедра біотехнології і мікробіології